The Use of Cartoon Clips to Teach Listening Skill - Cut Indira Dwi Putri; Iskandar Abdul Samad; Chairina Nasir (Research in English and Education Journal, 2017)
This experimental research aims at investigating the effect of teaching listening skill by using English Cartoon Clips on the first year students of SMA Negeri 1 Banda Aceh. Listening skill is one of important skills that students are required to master. As a matter of fact, students are commonly facing some difficulties on this skill. One group pre-test post-test design was used to analyze the significant effect. The data were gained quantitatively by administering pre-test, treatments and post-test. The result revealed that there was an improvement in students’ learning achievements focused on listening sub-skills which deals with its aspects, i.e. understanding the gist in listening and listening for details in the narrative genre. The finding was supported by the result of students’ pre-test and post-test scores. The mean of pre-test scores was 77.4, while the mean of post-test scores was 93.5. The gained score is 16.1. Moreover, the analysis of t-test showed that tscore ttable or 4.43 1.70 at the level of significance 0.05 with the degree of freedom (df) 25. It is clear that the alternative hypothesis (Ha) is accepted. Furthermore, based on the comparison between the mean score of each listening aspects of pre-test and that of post-test, it indicated that students gained a better achievement in identifying those listening sub-skills aspects. In brief, the application of English Cartoon Clips affected the students’ listening performance.